Strategi Penggunaan Bahasa Inggris Pramuwisata Pemula dalam Menjelaskan Obyek Wisata di kabupaten Bangli - Md. Yudyantara Risadi; Ni Kadek Herna Lastari (UHN IGB Sugriwa Denpasar, 2023)
One of the regencies in Bali that has cultural and spiritual tourist attractions is Bangli regency. The existence of these tourist attractions should also be complemented by human resources such as tour guides, which, of course, begins with beginner tour guides. The aim of this research was to determine the strategies used by beginner tour guides in using the English language in carrying out their duties, as well as the challenges and solutions in the process. This research was conducted qualitatively using observation, interviews, documentation, and literature review as the methods. The results of this study found that when using English, the tour guides employ strategies in the preparation, execution, and farewell stages. Each of these stages involves specific strategies that reflect their respective phases. The challenges faced by beginner tour guides include nervousness, incomplete mastery of the subject matter, and limited vocabulary. The proposed solutions include language training provided by relevant parties, continuous practice in the field, and learning from more experienced colleagues. These solutions should be tailored to each individual's capacity to adapt to their learning pace.